Two different liver-specific factors stimulate in vitro transcription from the human alpha 1-antitrypsin promoter. - Monaci, P (1988)
The region from -137 to -2 of the human alpha 1-antitrypsin (alpha 1AT) promoter directs liver-specific in vitro transcription. Two cis-acting elements, A and B, have been identified within this segment by site-directed mutagenesis. Competition with synthetic oligonucleotides corresponding either to the A or to the B sequence inhibits transcription from the wild-type promoter in vitro. Cis-linked A and B elements mediate liver-specific transcription from a truncated HSV-TK promoter in vitro. Five different proteins, LF-A1, LF-A2, LF-B1, LF-B2 and LF-C, bind to the alpha 1AT promoter in liver extracts. LF-A1 and LF-B1 are positive transcriptional factors which bind to the A and B elements respectively. Their absence in spleen provides an explanation for the liver specificity of transcription. A protein similar to LF-B2 is present in spleen. Binding of LF-B1 and LF-B2 to the alpha 1AT promoter is mutually exclusive, suggesting that LF-B2 might be a repressor.